Anterior shoulder instability: comparison between Latarjet open procedure and arthroscopic capsuloplasty - Vecchini, Eugenio; Ricci, Matteo; Chiappi, Jacopo; Ambrosini, Carlo; Fasoli, Giacomo; Crespan, Beatrice; Maluta, Tommaso; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2023)
Background: Latarjet surgery and capsuloplasty are both valid alternatives for the treatment of anterior shoulder instability with limited glenoid bone loss, although in literature there is extensive discussion on it. The purpose of this study was to compare the outcomes of these procedures in patients with similar lesions. Methods: Between January 2000 to October 2020, 59 nonconsecutive patients suffering from anterior shoulder instability were treated, 33 had arthroscopic capsuloplasty (Group 1) and 26 had open Latarjet procedure (Group 2). The Group 1 was composed by 12% of female and 88% of males with the mean age at surgery 25.6 +/- 9.07 (15-49 years). In the Group 2, the 100% of patients were males with mean age 32.42 +/- 10.74 (16-56). Rowe Score, UCLA score and WOSI score were used to test patients. Results: Only UCLA (average was 22.18 ± 6.13 for the Capsuloplasty and 26.76 ± 6.57 in the Latarjet, p = 0.01) and ROWE scores (average was 70.15 ± 24.75 in Latarjet and 50.15 ± 24.70 in Capsuloplasty, p = 0.002) showed a statistically significant difference between the two procedures, while the WOSI (mean results of Latarjet 0.31 ± 0.16 against 0.24 ± 0.09 of the capsuloplasty, p = 0.069) there was no significant difference between the two groups in question. Conclusions: Apparently, the Latarjet surgery is better in terms of instability recurrence compared to capsuloplasty but has higher rate of shoulder joint osteoarthtritis. However, there are no significant differences that could decree which procedure is better. (www.actabiomedica.it)